Department of Surgery, Orthopedics and Traumatology of Faculty of Postgraduate Education SE «Dnipropetrovsk medical academy of Health Ministry of Ukraine» - Desyateryk, V. I.; Mikhno, S. P.; Dunay, O. H. (Medicni Perspektivi, 2016)
Department of Surgery, Orthopedics and Traumatology of Faculty of Postgraduate Education SE «Dnipropetrovsk medical academy of Health Ministry of Ukraine»